Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatkan Hasil Belajar Siswa SMA Kelas X IPA Dharma Wanita Persatuan Pemprovsu Tahun 2022: (Application of the Jigsaw Cooperative Learning Model to Improve Student Learning Outcomes in Class X IPA Dharma Wanita Pemprovsu Association in 2022) - Dewi Yulika Harahap; Lidyah Rahmayani; Putri Bungsu Berutu; Indayana Febriyani Tanjung (BIODIK, 2023)
The objectives of this Classroom Action Research were to: 1) Improve student learning outcomes at the Dharma Wanita Association of North Sumatra Provincial Government 2) Improve students' abilities with the jiksaw type cooperative learning model. To achieve this goal, the study was designed in two cycles. The procedure for each cycle includes: 1) development of a problem focus, 2) planning of corrective actions, 3) implementation of actions, observations, and interpretations. The effectiveness of the actions in each cycle is measured from the results of observations and the results of the pretest and posttest abilities. Observational data in cycle I were described and interpreted and then reflected to determine corrective actions in cycle II. While the data in the form of pretest and posttest ability test results were analyzed by describing and comparing test scores in the initial conditions, cycle I, and cycle II. The completion limit that must be achieved by students in cycle II, namely: 100% of students are able to answer all pretest and posttest questions with a maximum of 2) all students achieve a maximum score of 80. Class Action Research regarding student activities while participating in learning, the results obtained were that classical completeness was 70% in the initial conditions, 70% in the first cycle, and 80% in the second cycle. Based on the results of this Classroom Action Research, it can be concluded that: The Application of the Jigsaw Type Cooperative Learning Model in the Ecosystem Concept to Improve Student Learning Outcomes at the North Sumatra Provincial Government's Dharma Wanita Association High School. Can improve learning outcomes and can change student learning patterns. Abstrak. Tujuan Penelitian Tindakan Kelas ini adalah untuk: 1) Meningkatkan hasil belajar Siswa SMA Dharma Wanita Persatuan pemprovsu 2) Meningkatkan kemampuan siswa dengan model pembelajaran kooperatif tipe jiksaw.Untuk mencapai tujuan, tersebut, penelitian didesain dalam dua siklus. Prosedur pada setiap siklus, mencakup tiap-tiap: 1) pengembangan fokus masalah, 2) perencanaan tindakan perbaikan, 3) pelaksanaan tindakan, observasi, dan interpretasi, Keefektifan tindakan pada setiap siklus diukur dari hasil observasi dan hasil tes kemampuan pretest dan postest. Data hasil observasi pada siklus I, dideskripsikan dan diinterpretasikan kemudian direfleksi untuk menentukan tindakan perbaikan pada siklus II. Sedangkan data yang berupa hasil tes kemampuan pretest dan post tes dianalisis dengan cara mendeskripsikan dan membandingkan nilai tes pada kondisi awal, siklus I, dan siklus II. Batas tuntas yang harus dicapai siswa pada siklus II, yakni: 100% siswa mampu menjawab semua soal pretest dan postest dengan maksimal 2)semua siswa siswi mencapai nilai yang maksimal yaitu80. Penelitian Tindakan Kelas mengenai aktivitas siswa selama mengikuti pembelajaran, diperoleh hasil bahwa ketuntasan secara klasikal pada kondisi awal sebesar 70%, pada siklus I sebesarg 70%, dan pada siklus II sebesar 80%. Berdasarkan hasil Penelitian Tindakan Kelas tersebut, dapat disimpulkan bahwa: Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Pada Konsep Ekosistem untuk Meningkatkan Hasil Belajar Siswa SMA Dharma Wanita Persatuan pemprovsu. Dapat meningkatkan hasil belajar dan dapat mengubah pola pembelajaran siswa.